Evaluation Of Drugs Use With Who Prescribing Indicator In Kuta Primary Health - Satrya Dewi, Dewa Ayu Putu; Arimbawa, Putu Eka; Jaelani, Abdul Khodir (Jurnal Endurance, 2018)
The Government of Indonesia has a lot of intervention for rationalizing drug use of all levels of health services including Primary Health Care. One of the programs of rational use of drugs at Primary Health Care is monitoring and evaluation of drug use conducted by pharmacist. The purpose of this research was to evaluate the rationality of drug usein Kuta Primary Health Care that review from WHO prescribing indicators and knowing the difference percentage of rationality of drug use between Kuta Primary Health Care. This research used cross sectional design research conducted in Kuta Primary Health Care on October 2017. Data analyzed using descriptive analysis and Kruskall-Wallis test. The average number of drug prescribed per en counter was 2.9. The percentage of drugs prescribed by generic drugs was 85.91percent. The percentage prescribed of encounters in which an antibiotic on ARI non Pneumonia was 29.94 pecent  and percentage prescribing antibiotic drugs in a non-specific diarrhea was 23.84 percent. The percentage prescribed of encounters injection was 0 percent. On the basic of the finding of this study the prescribed practices for polypharmacy, generic prescribing, and antibiotic shows deviation from the standard recommended by WHO and Directorate General of Pharmaceutical and Medical Devices Indonesia. These finding suggested increase health workers knowledge through scientific meetings or Focus Group Disscution (FGD) that can support a rational use of drugs in the Primary Health Care. Pemerintah Indonesia telah banyak melakukan intervensi untuk merasionalkan penggunaan obat dari segala tingkat pelayanan kesehatan termasuk Puskesmas. Salah satu program Penggunaan Obat Rasional (POR) di Puskesmas adalah monev penggunaan obat yang dilakukan oleh farmasis. Tujuan penelitian ini adalah melakukan evaluasi rasionalitas penggunaan obat di Puskesmas Kecamatan Kuta ditinjau dari indikator peresepan (% peresepan obat generik, % persentase antibiotik, % peresepan injeksi) dan mengetahui perbedaan persentase rasionalitas penggunaan obat antar Puskesmas Kecamatan Kuta. Penelitian ini menggunakan rancangan penelitian cross sectional yang dilakukan pada Puskesmas Kuta I, Kuta II, dan Kuta Utara pada bulan Oktober 2017. Analisis data menggunakan analisis deskriptif dan uji Kruskall-Wallis. Analisis deskriptif dari tenaga kesehatan menunjukkan bahwa, profesi Apoteker masih langka di Puskesmas Kecamatan Kuta yaitu hanya ada di Puskesmas Kuta 1 per November 2018. Hasil penelitian tiap parameter pada Puskesmas Kecamatan Kuta tidak ada yang memenuhi target kriteria POR dari target Dirjen Binfar kecuali parameter peresepan injeksi. Rata-rata obat tiap pasien adalah 2,9, % peresepan obat generik adalah 85,91%, % peresepan obat antibiotik pada ISPA non Pneumonia adalah 29,94%, % peresepan obat antibiotik pada diare non spesifik adalah 23,84%, dan % peresepan injeksi adalah 0%. Hal tersebut menunjukkan bahwa Puskesmas Kecamatan Kuta masih mengalami masalah polifarmasi dan penggunaan antibiotik berlebihan. Hasil penelitian ini dapat menunjukkan adanya kebutuhan untuk meningkatkan pengetahuan tenaga kesehatan melalui pertemuan ilmiah atau Focus Group Disscution (FGD) yang dapat mendukung penggunaan obat yang rasional di Puskesmas.